Investigation on the aggregation behavior of photo-responsive system composed of 1-hexadecyl-3-methylimidazolium bromide and 2-methoxycinnamic acid. Issue 84 (16th September 2015) - Du, Mingyong; Dai, Caili; Chen, Ang; Wu, Xuepeng; Li, Yuyang; Liu, Yifei; Li, Weitao; Zhao, Mingwei
<x xml:space="preserve">Abstract</x> Mechanism of the aggregation behavior for the photo-responsive system composed of 1-hexadecyl-3-methylimidazolium bromide and 2-methoxycinnamic acid.